Application of Capital Punishment for Narcotics Offenders in the Perspective of Responsive Law - Muhammad Alief Yunas Pahlevi; Catur Wido Haruni; Said Noor Prasetyo (Rechtsidee: Law Journal, 2023)
This study employs a normative legal research method, grounded in the Nonet and Selznick theory of responsive law, to examine the implementation of capital punishment for narcotics offenders in Indonesia. Evaluating the punitive measures through the lens of responsiveness to societal goals, participation of vulnerable groups, and legal institutions' balanced response, the research highlights the need for a nuanced approach. Findings indicate that the current use of capital punishment lacks effectiveness and contradicts human rights principles. The study suggests a reassessment, prioritizing rehabilitation and decriminalization for a more humane and sustainable approach to combating narcotics trafficking.